2011
DOI: 10.1590/s0100-06832011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Relações solo-paisagem em uma topossequência sobre substrato granítico em Santo Antônio do Matupi, Manicoré (AM)

Abstract: RESUMOConsiderando as dimensões da região amazônica e a necessidade de estudos que estabeleçam conexões entre os solos e a expressão da paisagem, o objetivo deste trabalho foi estudar as relações solo-paisagem em uma topossequência sobre substrato granítico em Santo Antônio do Matupi, Manicoré, AM. Foi estabelecido um caminhamento de 3.000 m a partir do "espigão" da vertente, no seu sentido mais suave, com identificação dos segmentos da vertente com base na "quebra" do declive do terreno. Foram abertas trinche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
3
9
0
10
Order By: Relevance
“…In relation to the sampled profiles, for the granulometric fractions in the different physiographic environments, the dominance of silt fraction was observed in almost all the profiles (Table 2). In natural field / forest transition environments this behavior of silt dominance is common due to the alluvial nature of the sediments that compose the source material Brazil (1978), similar results were also obtained by Martins et al (2006) and Campos et al (2011) studying natural fields. It was observed that the clay content tends to increase from the high relief to floodplain / dry land physiographies.…”
Section: Physical Attributessupporting
confidence: 67%
See 3 more Smart Citations
“…In relation to the sampled profiles, for the granulometric fractions in the different physiographic environments, the dominance of silt fraction was observed in almost all the profiles (Table 2). In natural field / forest transition environments this behavior of silt dominance is common due to the alluvial nature of the sediments that compose the source material Brazil (1978), similar results were also obtained by Martins et al (2006) and Campos et al (2011) studying natural fields. It was observed that the clay content tends to increase from the high relief to floodplain / dry land physiographies.…”
Section: Physical Attributessupporting
confidence: 67%
“…In addition Campos et al (2011) emphasizes that in this part of the Amazon it is common to find environments with soils in gently wavy to corrugated relief with different characteristics of the environments initially mentioned, the presence of granite and the variations of the relief favored the presence of dystrophic soils at the top Rhodic Ferralsol and eutrophic soils Typic Hapludox at the transport base.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…As temperaturas médias anuais alteram entre 25 e 27 ºC e a umidade relativa permanecem entre 85 e 90% (Brasil, 1978). O solo foi classificado como Latossolo Amarelo (Campos et al 2011b) e a vegetação característica dessa região é Floresta Tropical Densa, formada por árvores adensadas e multiestratificadas de 20 a 50 m de altura (Brasil, 1978).…”
Section: Methodsunclassified